School Based Management (SBM) to Improve Quality of Education in KHM Nur Junior High School Surabaya - Ulfa Suhroh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Currently, education management in Indonesia recognizes two mechanisms, namely centralization and decentralization system, in the centralized system of education administration regulated by the central government. This study aims to find out how the implementation of School Based Management (SBM) in KHM NUR Junior High School Surabaya, knowing what programs are implemented in KHM NUR Junior high School Surabaya and aims to determine what factors that support and hinder the implementation of School Based Management (SBM) in an effort to improve the quality of education at KHM NUR Junior High School Surabaya. The type of research used in this study is Field Research, which is studying intensively about the background of the present state, in the interaction of a social, individual, group, institution, and society. Technique of data analysis used qualitative descriptive. The findings of this study can be concluded; first: Implementation of School Based Management (SBM) at KHM. NUR Junior High School Surabaya has been well scheduled. Second: The programs that have been implemented as the implementation of School Based Management (SBM) in KHM. NUR Junior High School Surabaya in academic and non-academic field. Third: Supporting and inhibiting factors in the implementation of School Based Management (SBM) in KHM. NUR Junior High School Surabaya among others comes from the intern and extern of the school. Keywords: School Based Management (SBM), Quality of Education